Theorising Media : Power, form and subjectivity - Corner, John, 1943- (Book collections on Project MUSE., 2014)
Over the past thirty years or so, John Corner has had a persistent regard for the value of conceptual terms in media research ... Theorising Media is consistent with this abiding concern and ... in many ways this new book marks its culmination.